2008
DOI: 10.1002/cncr.23783
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, randomized clinical trial comparing zoledronic acid versus observation in patients with asymptomatic myeloma

Abstract: BACKGROUND.Bisphosphonates (BPs) are effective in the prevention and treatment of skeletal‐related events (SREs) in patients with symptomatic myeloma who are receiving chemotherapy. Recent data also suggest a possible antineoplastic activity of BPs. Few studies published to date have explored the role of BPs in patients with untreated, asymptomatic myeloma (AM). No data are available on the efficacy of zoledronic acid in these patients.METHODS.The authors conducted a prospective, multicenter, open‐label, phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(115 citation statements)
references
References 48 publications
4
109
1
1
Order By: Relevance
“…Prognostic models for predicting asymptomatic MM progression, 8,12,15 including the model described in the current study, would allow the identification of low-risk patients who harbor a very indolent disease similar to MGUS and high-risk patients who might benefit from close follow-up and who may be optimal candidates for experimental therapies aimed at delaying the progression of MM. [35][36][37][38][39][40][41] …”
Section: Discussionmentioning
confidence: 99%
“…Prognostic models for predicting asymptomatic MM progression, 8,12,15 including the model described in the current study, would allow the identification of low-risk patients who harbor a very indolent disease similar to MGUS and high-risk patients who might benefit from close follow-up and who may be optimal candidates for experimental therapies aimed at delaying the progression of MM. [35][36][37][38][39][40][41] …”
Section: Discussionmentioning
confidence: 99%
“…In addition, ZOL was administered for only 12 months, and it is possible that a longer duration of treatment may have been more effective. 62 Indeed, in a pilot study of patients who were receiving initial chemotherapy for MM (N ¼ 94), ZOL (4 mg per month iv) significantly improved the 5-year OS rate from 46% to 80% compared with chemotherapy alone (P < .01). 63 Similarly, a pilot study in patients with bone metastases from bladder cancer (N ¼ 40) demonstrated that ZOL (4 mg per month iv for 6 months) significantly reduced the risk of SRE by 58% (P ¼ .008), reduced pain scores by 1.42 units versus placebo (P ¼ .015), and improved the 1-year OS rate 6-fold (P ¼ .02) versus placebo.…”
Section: Anticancer Effects In the Advanced Disease Settingmentioning
confidence: 97%
“…Several studies have also evaluated the antitumor effect of bisphosphonate monotherapy in patients with asymptomatic/smoldering MM. [11][12][13][14][15][16] Although these studies demonstrated some benefit of bisphosphonates on bone resorption, no clear tumor responses or benefits in terms of progression-free or overall survival were observed. Patients with smoldering MM probably do not constitute the ideal target population for such studies because, given their low rate of progression, 24 a large number of patients and long follow up would be needed to demonstrate a survival benefit for a drug that would have only a minor antitumor activity, if any.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…Moreover, in patients with smoldering MM, treatment with bisphosphonates did not delay transformation into symptomatic disease although it was associated with a reduction in the onset of skeletal-related events. [11][12][13][14][15][16] Accordingly, the real anti-tumor effect of bisphosphonates remains to be elucidated. Patients at biochemical relapse, in whom the standard of care is to delay treatment until symptoms emerge, represent an ideal group to investigate the anti-myeloma effect of ZA.…”
Section: Introductionmentioning
confidence: 99%